Immunohistochemical evaluation of E-cadherin in oral epithelial dysplasia and squamous cell carcinoma - Jaishree Sharma; Manish Bhargava; Shivani Aggarwal; Ashim Aggarwal; Anchal Varshney; Disha Chopra (Wolters Kluwer Medknow Publications, 2022)
Aim: To evaluate the expression of E-cadherin (E-cad) in oral epithelial dysplasia (OED) and oral squamous cell carcinoma (OSCC). Material and Method: Immunohistochemistry was used to detect E-cad expression in 20 cases each of normal oral mucosa, oral epithelial dysplasia and squamous cell carcinoma. Statistical Analysis Used: Inferential statistical methods for statistical analysis used were Chi-square test for comparison of the frequency between different severity of dysplasia and OSCC. Results: Upon assessing the expression of E-cad in OED and OSCC, increase in E-cad immunoreactivity was seen in early lesions. However, the expression of E-cad decreased significantly as the grade of dysplasia increased. Conclusion: We observed a significant decrease in E-cad expression from dysplasia to poorly differentiated squamous cell carcinoma suggesting that loss of expression of E-cad is closely related to carcinoma.